Palladium-Catalyzed/Copper-Mediated Desulfurization and Arylation of Quinoline-2-(1H)-thione for Rapid Access to Quinoline Derivatives - Lu, Hai-Long; Guo, Fu-Hu; Wang, Tong-Lin; Wang, Xi-Cun; Quan, Zheng-Jun (Synthesis, 2020)
An efficient method for carbon–carbon bond formation is described. The process employs the palladium-catalyzed and copper-mediated cross-coupling of quinoline-2-(1H)-thiones with arylboronic acids or alkynes through C–S bond cleavage without an inert atmosphere. The method provides rapid and general access to a diverse range of 2-substituted quinolines in a single step from a wide range of quinoline-2-(1H)-thiones and arylboronic acids or alkynes.
Keywords: C–S bond cleavage; arylboronic acids; alkynes; quinoline-2-thiones; Liebeskind–Srogl cross coupling